Bone turnover during short course prednisolone treatment in patients with chronic obstructive airways disease. Issue 6 (June 1992) - Morrison, D; Ali, N J; Routledge, P A; Capewell, S
Abstract : BACKGROUND: Although osteoporosis is a well known side effect of long term prednisolone, the effects of a short course are less clear. Biochemical markers of bone turnover were therefore studied in 10 men with chronic obstructive airways disease who required assessment of "steroid reversibility" (mean age 65 years, mean FEV1 1.2 1). METHOD: Patients received, single blind, two weeks of placebo, four weeks of prednisolone 20 mg/day, and then two further weeks of placebo. RESULTS: The mean (SD) fasting urinary hydroxyproline:creatinine ratio, a marker of bone resorption, increased by 65% with prednisolone (from 8.9 (5.7) to 14.7 (8.5) mumol/mmol) and returned to baseline after placebo. Serum alkaline phosphatase, a marker of net bone formation, fell after prednisolone by 28% (from 113 (41) to 81 (30) IU/1). Substantial changes occurred after only two weeks of prednisolone. Serum osteocalcin, calcium, and phosphate concentrations did not change significantly. CONCLUSIONS: Short courses of prednisolone increased bone resorption and inhibited bone formation after two and four weeks.